MATHEMATICAL MODEL ON THE FEASIBILITY OF NGV FILLING STATION CONSTRUCTION FOR PUBLIC TRANSPORT FUEL SUBSTITUTION IN JABOTABEK AREA - Yusep K Caryana (Scientific Contributions Oil and Gas, 2002)
A key factor that should be taken into account in implementing public transport fuel substitution in Jabotabek area is the feasibility of NGV (new) filling stations construction. This needs to be considered in order that the supply of NGV in the area can be secured. Otherwise, additional demand of NGV (CNG and/ or LPG) for the substitution will not be met. A mathematical model of the feasibility of NGV filling station construction has been developed as a rule of thumb of the construction. The model is then applied to select the location of NGV filling station based on public transport population in Jabotabek area.